Gonadosomatic index and fecundity of Heteropneustes fossilk (Bloch) (Pisces : Heteropneustidae) from Hussain Sagar, Hyderabad - Reddy, Y Siva; Rao, M Babu (Indian Journal of Fisheries, 2011)
The gondosomatic index of the specimens of Heteropneustes fossiles (Bloch) from Hussain Sagarlake, Hyderabad, indicated their spawning season from April to July. Fecundity ranged from 1 446 to30 050. This was less than the specimens of Cultack and Barrackpore but more than those of Kolleru lake.No positive correlation was noticed between the total length or the weight of the fish and fecundity. Thespecimens of Hussun Sagar (length range 150- 340 mm) took more time to attain maturity than those ofKolleru lake (length range 100 - 260 mm).